Azimuthal Distribution in Heavy-Ion Collisions - Pandis, G.; Das Gupta, S. (HNPS Advances in Nuclear Physics, 2020)
We consider recent experimental data on azimuthal distributions of particles seen in heavy-ion collisions at 35 MeV/nucleon and at 50 MeV/nucleon. For 12C on 12C at 50 MeV/nucleon lab energy, the distribution shows features characteristic of flow; for 12C on 197Au experimental data show features characteristic of rotation. For 40Ar on 51V at 35 MeV/nucleon, effects of both flow and rotation are seen. In magnitudes the effects are small. We find that BUU calculations are able to reproduce these results.